Prevalence and ecological factors affecting the distribution of plant-parasitic nematodes in Prunus groves in Spain - Ilenia Clavero-Camacho; Antonio Archidona-Yuste; Carolina Cantalapiedra-Navarrete; Pablo Castillo; Juan Emilio Palomares-Rius (Journal of Integrative Agriculture)
A wide survey was conducted to study plant-parasitic nematodes (PPNs) associated with Prunus groves in Spain. This research aimed to determine the prevalence and distribution of PPNs in Prunus groves, as well as the influence of explanatory variables describing soil, climate and agricultural management in structuring the variation of PPNs community composition. A total of 218 sampling sites were surveyed and 84 PPN species belonging to 32 genera were identified based of an integrative taxonomic approach. PPN species considered as potential limiting factors in Prunus production, such as Meloidogyne arenaria, M. incognita, M. javanica, Pratylenchus penetrans and P. vulnus, were identified in this survey. Seven soil physico-chemical (C, Mg, N, Na, OM, P, pH and clay, loamy sand and sandy loam texture classes), four climate (Bio04, Bio05, Bio13 and Bio14) and four agricultural management variables (grove-use history less than 10 years, irrigation, apricot seedling rootstock, and Montclar rootstock) were identified as the most influential variables driving spatial patterns of PPNs communities. In particular, younger plantations showed higher values for species richness and diversity indices than groves cultivated for more than 20 years with Prunus spp. Our study increases the knowledge of the distribution and prevalence of PPNs associated with Prunus rhizosphere, as well as on the influence of explanatory variables driving the spatial structure PPNs communities, which has important implications for the successful design of sustainable management strategies in the future in this agricultural system.